Business models for the social mobile cloud : transform your business using social media, mobile Internet, and cloud computing - Shelton, Ted, 1966- (Hoboken, N.J. : John Wiley & Sons, 2013)
"The combined impact of social technologies, the mobile Internet, and cloud computing are creating incredible new business opportunities. They are also destroying unprepared companies, transforming industries, and leaving behind workers who are unwilling or unable to adapt. Business Models for the Social Mobile Cloud reveals a compelling view from PwC of how the social mobile cloud and a combination of new technology changes are key players in a digital transformation in business and society that is moving more quickly and cutting more deeply than any technology transformation ever seen"--Provided by publisher.
Preface: There's an app for that! -- Introduction: Turning inside out -- A remote control for the world -- Social means connected : compete with yourself, collaborate with others -- Mobile : the great untethering -- Plug yourself into the cloud -- Adapt : adapting to change -- Persistent digital engagement : the new digital consumer -- Digitization : the rising value of information in products and services -- Crowd storming, crowd sourcing, collaboration, co-creation -- Hierarchy will yield to networks, remaking organizations -- How we buy : redefining shopping and payment -- The game of work, the work of game -- Work and the workplace reimagined -- Understanding change -- Undoing our resistance to learning -- Systems thinking -- Decision making -- Seven steps to adaptability -- Afterword: Digital transformation : what will you and your business look like 10, 20, 50 years from now? -- Appendix: PwC thought leadership on social, mobile, analytics, cloud (SMAC).
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Information technology -- Management; Internet marketing; Social media; Cloud computing; Information technology -- Management; Internet marketing; Social media; Cloud computing; BUSINESS & ECONOMICS -- E-Commerce -- Internet Marketing; BUSINESS & ECONOMICS -- Mail Order; BUSINESS & ECONOMICS -- Marketing -- Direct; BUSINESS & ECONOMICS -- Marketing -- Multilevel; BUSINESS & ECONOMICS -- Marketing -- Telemarketing; Cloud computing; Information technology -- Management; Internet marketing; Social media; Information technology / Management; Internet marketing; Social media; Cloud computing; Electronic books